(untitled) (@limentech, Ciencia y Tecnología Alimentaria, 2023)
The objective of the research was to implement a Good Manufacturing Practices Manual in the FOCAZNOM association to comply with the quality standards established in ARCSA-DE-067-2015-GGG. A diagnosis of the preliminary conditions of the Sacha Inchi-based snack production line was carried out through a verification instrument known as a check list based on the documentation, requirements for facilities, equipment and utensils, and hygienic requirements for personal manufacturing, raw materials and inputs, production operations, packaging, labeling and packaging, storage, distribution and transportation to identify compliance with good manufacturing practices. It was found that 64% of the evaluated requirements do not meet the requirements established in ARCSA-067-2015-GG for the implementation of a Good Manufacturing Practices manual because the previous microbiological analyzes showed high microbial load in mesophilic aerobes, molds and E. coli. With respect to the training phase for the actors involved in the production process, a percentage of 83% was achieved in compliance with the quality indicators and in the microbiological analyzes the microbial load was generally reduced. It is concluded that the measures used in this research in relation to the quality and safety of the snack were met with a product suitable for consumption.